Cryptanalysis of an image encryption algorithm based on DNA encoding. (1st October 2017) - Akhavan, A.; Samsudin, A.; Akhshani, A.
Highlights: This paper investigates security of a recently proposed image encryption algorithm. The novelty of the research lies in the new efficient cryptanalysis method. The proposed cryptanalysis method can successfully recover plain image from cipher image. The cryptanalysis of the algorithm under study is possible with only few chosen plain images. The proposed cryptanalysis method is based on chosen plaintext attack. Abstract: Recently an image encryption algorithm based on DNA encoding and the Elliptic Curve Cryptography (ECC) is proposed. This paper aims to investigate the security the DNA-based image encryption algorithm and its resistance against chosen plaintext attack. The results of the analysis demonstrate that security of the algorithm mainly relies on one static shuffling step, with a simple confusion operation. In this study, a practical plain image recovery method is proposed, and it is shown that the images encrypted with the same key could easily be recovered using the suggested cryptanalysis method with as low as two chosen plain images. Also, a strategy to improve the security of the algorithm is presented in this paper.